Are Transfer Students Different? An Examination of First-Year Grades and Course Withdrawals - Stewart, Jo; Martinello, Felice (Canadian Journal of Higher Education, 2012)
Using data from several introductory-level courses at one Canadian university, community college transfer students were compared to transfer students from other universities and to non-transfer students on a number of measures of academic success. The three groups did not differ significantly in terms of course withdrawal rates, and final course grades for college transfer students were not significantly different from those of non-transfer students. However, students who had transferred from other universities received higher final grades. Mid-course grades and gender comparisons are discussed, as are policy implications and suggestions for future research.